Conteúdo globalizado para a alfabetização: uma proposta de educação patrimonial - Basso, Marluze Parizotto (2024)
“Globalized Content for Literacy: a Proposal for Heritage Education” refers to the result of the dissertation of the Professional Master’s Course of the Postgraduate Program in Cultural Heritage, in the Area and Line of Research in History and Cultural Heritage, in which the product created was a didactic activity book. Preserving memory is an important activity and commitment for future generations. We believe it is important to create a culture of preserving memories and popular knowledge, of what we will inherit from our grandparents and/or parents, as it provides us with a sense of social belonging, as well as our identity, both individual and collective. In this way, heritage education allows these cultural and historical legacies to be preserved, protected and re-signified. It is necessary to develop in schools, with our students, the recognition of the assets we possess. These assets are responsible for development in all spheres: social, cultural, economic and natural. We need to work with students from an early age on the need to look at and get to know the region to which they belong. To this end, bibliographical sources were used in carrying out this work, such as scientific articles, book chapters, publications with legislation, teaching manuals, etc. in which experiences with heritage education were highlighted, such as in the dissertations that are part of the productions of the Master's Degree in Cultural Heritage, among others. The development of this research work and the resulting product aimed to meet a demand for the lack of applied teaching material, that is, teachers find it difficult to align the contents of the National Common Curricular Base (BNCC) with the Heritage Education proposal, which was implemented as a Municipal Law in 2022 (Law No. 2,727 of October 13, 2022), which includes Heritage Education in the School Curriculum and in classes taught in public schools in the education network in the Municipality of Faxinal do Soturno, RS. This policy was constructed in recent years together with the consolidation of the Quarta Colônia Geopark.